Exploring the Development of Bazaar-type Economy under the Night Economy: A Case Study of Chengdu, China - Zhou, Shuying; Sun, Yaqi (Transactions on Economics, Business and Management Research, 2024)
With the development of Chengdu's night economy, the internet-famous street food stalls have become nationally famous and a symbol of Chengdu's tourism and entertainment. Under the influence of COVID-19, more and more middle and low-level urban migrant workers are becoming unemployed. However, as a city famous for its night market, the stallholder operation finds another new way for the unemployed to make a new business. This article will focus on the current situation of night market bazaar-type economy in Chengdu under the background of night economy and the factors influencing night market bazaar-type economy. Therefore, by analyzing the current situation of night market bazaar-type economy in Chengdu and combining it with its inherent characteristics, suggestions for improvement are proposed.